DESKRIPSI PEMAHAMAN KONSEP PADA MATERI UNSUR, SENYAWA DAN CAMPURAN SMP NEGERI 4 SUNGAI RAYA - Juniarti, Ahan; Harun, A. Ifriany; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study was to describe the student?s conceptual understanding on the material of element, compound and mixture in grade VII of  SMP Negeri 4 Sungai Raya. A descriptive method was employed in this study. As many as 35 students participated as the subject. Essay test and interview guidelines were used to collect data. According to data analysis the average of student?s conceptual understanding was 34,28 % which categorized as poor. The percentage of student?s understanding in (1) the element concept was 55 % (2) the compound concept was 41,42 %; (3) the mixture concept was 53,57 %; (4) the properties of the metal element concept was 82,86 %; (5) the homogeneous mixture concept was 11,43 %; (6) the heterogeneous mixture concept was 12,86 %; (7) the colloid concept was 33,57 %; (8) the suspension concept was 14,28 %; (9) the element symbol concept was 27,86 %; and (10) nomenclature binary compounds concept was 1,9 %.Keywords: conceptual understanding, element, compound, mixture